Phenothiazinium Photosensitizers Associated with Silver Nanoparticles in Enhancement of Antimicrobial Photodynamic Therapy - Rigotto Caruso, Glaucia (Antibiotics (Basel), 2021)
Antimicrobial photodynamic therapy (APDT) and silver nanoparticles (AgNPs) are known as promising alternatives for the control of microorganisms. This study aims to evaluate the antifungal activity of APDT, particularly by using the association of low concentrations of phenothiazinium photosensitizers (PS) methylene blue (MB), new methylene blue N (NMBN), and new methylene blue N Zinc (NMBN-Zn) in association with biosynthesized AgNPs. The AgNPs were characterized by UV-Vis spectrophotometry, transmission electron microscopy, and the dynamic light scattering method. The minimum inhibitory concentration of compounds in APDT against Candida albicans and Fusarium keratoplasticum was obtained and the Fractional Inhibitory Concentration Index determined the antifungal effect. The toxicity of compounds and associations in APDT were evaluated in Galleria mellonella. The AgNPs presented a surface plasmon band peak at 420 nm, hydrodynamic diameter of 86.72 nm, and zeta potential of −28.6 mV. AgNPs-PS showed a wider and displaced plasmon band peak due to PS ligands on the surface and decreased zeta potential. AgNPs-NMBN and AgNPs-NMBN-Zn associations presented synergistic effect in APDT with 15 J cm(−2) against both fungi and did not show toxicity to G. mellonella. Hence, the enhancement of antifungal activity with low concentrations of compounds and absence of toxicity makes APDT with AgNPs-PS a promising therapeutic alternative for fungal infections.